Therapeutic potential and mechanistic insights of astragaloside IV in the treatment of arrhythmia: a comprehensive review - Chen, Meilian; Fu, Binlan; Zhou, Hao; Wu, Qiaomin (Frontiers in Pharmacology, 2025)
Arrhythmia, a common cardiovascular disorder, results from disturbances in cardiac impulse generation and conduction, leading to decreased cardiac output and myocardial oxygenation, with potentially life-threatening consequences. Despite advancements in therapeutic approaches, the incidence and mortality associated with arrhythmia remain high, and drug-related adverse effects continue to pose significant challenges. Traditional Chinese Medicine (TCM) has attracted considerable attention for its potential as a complementary and alternative approach in treating cardiovascular diseases, including arrhythmia. Astragalus, a prominent herb in TCM, is commonly used in clinical practice for its multi-faceted therapeutic properties, encompassing anti-arrhythmic, cardiotonic, anti-inflammatory, and immunomodulatory effects. Astragaloside IV, a primary active compound in Astragalus membranaceus, has demonstrated cardioprotective effects through mechanisms such as antioxidant, anti-inflammatory, and anti-apoptotic activities. Although evidence suggests that astragaloside IV holds promise in arrhythmia treatment, comprehensive reviews of its specific mechanisms and clinical applications in arrhythmia are scarce. This review systematically explores the pharmacological properties and underlying mechanisms of astragaloside IV in arrhythmia treatment. Utilizing a targeted search of databases including PubMed, Web of Science, Cochrane Library, Embase, CNKI, and Wanfang Data, we summarize recent findings and examine astragaloside IV’s potential applications in arrhythmia prevention and treatment. Our analysis aims to provide a theoretical foundation for the development of novel arrhythmia treatment strategies, while offering insights into future research directions for clinical application.